Assessment of diastasis recti abdominis: Clinimetric properties of four measuring instruments - Ojukwu, Chidiebele; Ezeigwe, Anne; Ezeigwe, Chukwudi; Ugwuonye, Chioma (International Journal of Health Sciences, 2023)
Objective: The aim of the study was to determine the intra- and inter-rater reliability of palpation technique, digital calipers, and diastometer, as well as their concurrent validity against ultrasound imaging. Methods: Ninety consenting parous women (20–45 years), recruited from a postnatal clinic in Enugu, Nigeria, participated in this observational study. Two physiotherapists and a sonographer measured their inter rectus distance at the level of the umbilicus, 4.5 cm above and below it, respectively, using each of the four modalities. The intrarater measurements were taken at a week’s interval. Data were analyzed with descriptive and inferential statistics of intraclass correlation coefficient and paired samples T-test, at an alpha level set at P < 0.05. Results: It showed the palpation technique (r = 0.749–0.967 and 0.658–0.917), digital calipers (r=0.750–0.955 and 0.685–0.904), and diastometer (r=0.762–0.958 and 0.471–0.902) demonstrated good inter- and intra-rater reliability. The concurrent validity of the palpation technique, digital calipers, and diastometer against the USI was poor at all three reference points. Conclusion: Palpation technique, digital calipers, and diastometer are reliable tools but not valid substitutes to ultrasound imaging for the clinical measurement of diastasis rectus abdominis